Interaksi antara model pembelajaran inkuiri terbimbing dan discovery dengan gaya belajar mahasiswa terhadap kemampuan berpikir kritis matematis - Ade Evi Fatimah; Azrina Purba (Journal of Didactic Mathematics, 2022)
This study aims to determine whether there is an interaction between the Inquiry and Discovery learning models with learning styles on the mathematical critical thinking skills of students of the STKIP Al Maksum Science Education study program in basic mathematics courses. This research was conducted in the even semester of the 2021-2022 academic year with a population of 109 students and a sample of 80 students. The research instrument used was in the form of mathematical critical thinking ability test questions. The research method used is a correlational method with a quantitative approach. This study used a quasi-experimental design. The research data were processed and analyzed using the 2x2 ANOVA statistical test. The results of the study show that there is an interaction between the Inquiry and Discovery learning models with learning styles on the mathematical critical thinking skills of Science Education students.